The Application of Problem-Based Learning Method for Hygiene Sanitation Learning Eyes - Siregar, Azwar; Nurlela, Luthfiyah; Marniati, Marniati; Rijanto, Tri; Munoto, Munoto (International Journal for Educational and Vocational Studies, 2020)
The post-millennial generation or currently known as the Z generation, is the generation born in the 2000s, the future generation born in the Internet age. This post-millennial generation does not like rigid rules, tends to think creatively and openly and is very easy to comment on. An important point in dealing with the post-millennial generation by providing specific direction for understanding ethics in social life. In the learning process, post millennial generation has visual characteristics, tries and sees the results of the process, wants the teacher as a facilitator, learning starts with "how", and is very easy to get information / knowledge. This is a challenge in determining the right learning strategy for them. With the problem-based learning method it is expected that students / vocational high school (SMK) students will be able to create something different to produce rewards in the form of money as well as personal satisfaction and freedom. Students are required to understand the importance of maintaining health by maintaining and protecting food hygiene, through controlling environmental factors that can or can cause illness and health problems.